Influence of ytterbium impurity on luminescent properties of ZnSe〈Al〉 crystals - Makhniy, V.P.; Vakhnyak, N.D.; Kinzerska, O.V.; Senko, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The influence of Yb impurity on evolution of luminescent properties of zinc selenide crystals doped with Al in the growth process is discussed. It was ascertained that diffusion of Yb impurity in a closed volume from vapor phase of ZnSe〈Al〉 substrates causes “quenching” the yellow-green band and appearance of intensive blue luminescent band that has exciton nature.